Genetic diversity of blue-spotted mudskipper (Boleophthalmus boddarti) populations in Gulf of Thailand - Theeranukul, Pachoensuk; Watabe, Shugo; Ikeda, Daisuke; Maltagliati, Ferruccio; Kettratad, Jes; Piyapattanakorn, Sanit (Agriculture and Natural Resources, 2021)
Environmental changes and the reduction of habitat can threaten populations of mudskippers, which have a distinct life cycle compared with other fish species. Genetic diversity and structure are crucial information for the conservation plan of this species. The genetic diversity was investigated on the blue-spotted mudskipper, Boleophtalmus boddarti, in the Gulf of Thailand. In total, 178 fish were collected from six locations in the Gulf. Based on the 320 bp sequences of the mitochondrial control region of the 55 haplotypes observed, the most common was in 88 fish from all locations. Total haplotype diversity and nucleotide diversity values (mean ± SD) were h = 0.751 ± 0.036 and π = 0.0069 ± 0.0001, respectively. There was a significant (p = 0.011) difference in π between inner and outer Gulf samples. Although the analysis of molecular variance suggested the absence of genetic structuring within the Gulf, two clear groups of haplotypes were evident in the median-joining network of haplotypes. Group I included haplotypes from all locations and group II was identified by haplotypes with an additional adenine at the 16078th position based on the mitochondrial genome sequence of B. boddarti (Accession no. KF87427). The results of the nonmetric multidimensional scaling and Bayesian assignment test were indicative of genetic divergence between the inner and outer Gulf, suggesting that despite the high potential for dispersal of planktonic larvae, water currents may act as a physical barrier to gene flow in the study area. The observed signals of population divergence between B. boddarti from the inner and outer Gulf of Thailand may account for the presence of this oceanographical barrier. Mismatch distributions, based on the observed number of differences among haplotype pairs, produced a unimodal distribution with a peak close to the y-axis, suggesting recent demographic expansion. The results could augment future study with baseline information on the maternal genetic variation and structure of the blue-spotted mudskipper, B. boddarti, populations in the Gulf of Thailand.